PERSEPSI AL-QUR’AN TERHADAP DINASTI POLITIK (Tinjauan Surah Al-Baqarah Ayat 124 dan At-Taubah Ayat 12 dan 23 Perspektif Tafsir Al-Misbah) - Pimpinan Abaik Simamora; Diki Saputra Siregar; Achyar Zein Siregar; Babang Prima Nugraha (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
The purpose of this study is to analyze political dynasties based on the Qur'an, Verse 124 of Surah Al-Baqarah and Verses 12 and 23 of Surah At-Taubah from the Perspective of Al-Misbah by Quraish Shihab. The focus of this study includes aspects of the interpretive analysis of the two verses related to political dynasties. The issue of traditional legislation is the regulation of the distribution of power in a rough period because it only focuses on blood or relatives to control power. The author of this article explains the research material that he wants to discuss by collecting various library sources based on primary and secondary data or applying the concept of qualitative research and a data collection approach based on literature studies. The important information used is the Tafsir Al-Misbah by Quraish Shihab, while the selected information is in the form of various primary data that correlate with the research. Based on the research analysis, several findings were obtained. First, power and leadership come from God and are not privileges based on blood, kinship, or lineage.